Evaluation of Physical and Mental Health in Adults Who Underwent Limb-Lengthening Procedures with Circular External Fixators During Childhood or Adolescence - Alessandro Depaoli; Marina Magnani; Agnese Casamenti; Marco Ramella; Grazia Chiara Menozzi; Giovanni Gallone; Marianna Viotto; Gino Rocca; Giovanni Trisolino (MDPI AG, 2024)
Background: Lower limb length discrepancy (LLD) in children and adolescents, often due to congenital or acquired conditions, is treated to achieve limb equality and alignment, optimizing function and minimizing cosmetic concerns for an active adulthood. This study evaluated the Health-Related Quality of Life (HRQoL) and physical functioning of adults who underwent unilateral limb lengthening with circular external fixators (EFs) in childhood. Methods: Fifty patients treated at a median age of 14.9 years completed the Short Form 36 (SF-36) and Stanmore Limb Reconstruction Score (SLRS) questionnaires in adulthood, with a median follow-up of 8.9 years. Results: Among the 50 patients, 38 underwent a single limb lengthening (21 tibia, 12 femur, 5 both), while 12 required multiple cycles. The median residual LLD was 0.4 cm, with 12 patients (24%) having over 2 cm. Complications occurred in 67% of procedures, mainly due to prolonged healing. Physical and mental health scores were significantly lower than normative data. The mean Physical Component Summary was 52.2 ± 7.2 (p = 0.20). The mean Mental Component Summary was 43.9 ± 8.6 (p = 0.001), notably lower in congenital LLD cases. Many SLRS items (Pain, Social, Physical Function, Work, and Emotions) strongly correlated with SF-36 items. Conclusions: Adults treated with distraction osteogenesis for congenital LLD show normal physical but lower mental health scores compared to peers. Lengthening procedure characteristics did not significantly impact mental health. Routine psychological and social assessments are recommended to prevent long-term distress by providing appropriate support.